Students’ Abilities and Difficulties in Comprehending English Reading Texts at Second Grade Students’ of SMA Negeri 1 Sakra Timur - Aini, Rodiyathul (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2024)
Reading is one of the four language skills taught in English learning process. Reading comprehension is the process of making meaning from the texts. Reading comprehension is the ability of the students to read the English reading texts, process the texts, and understand its meaning and integrated with what the reader already knows. The students had still low ability and high difficulties in comprehend the text. This study deals with the abilities and difficulties of the students in comprehending English reading texts. This research study aimed (a) to know the students’ reading abilities in comprehending English text, (b) to find out the students’ difficulties in comprehending English text, (c) to identify factors of causing the students’ difficulties in comprehending English text. The research employed qualitative research method. Data were collected through documentation/worksheet test and interview by 25 students’ and English teacher at senior high school in Sakra Timur. Among other findings, the present study reports that the students’ ability in comprehending English reading texts focus on descriptive text was still low. They had got low ability because they had high difficulties in comprehending English text. The difficulties faced by the students were determining main idea, understanding vocabulary, difficulties in making inference, and to looking for the detail information. The factors were causing the students’ difficulties in comprehending consist of two factors internal and external. The internal factors consist of the student difficulties in understanding long sentence, inadequate instruction presented by teacher, and difficulties in understanding vocabulary). The external factor consists of school and house environment. The other problem is the students’ lack of motivation, lack of interest in English, and lack of participant in English learning process. Their low in reading comprehension was due to their difficulties in comprehension.